Soil Carbon Storage Potential in Campus Green Spaces: A Case Study At Campus 2 Of Muhammadiyah University of Palangkaray: POTENSI SIMPANAN KARBON TANAH PADA RUANG TERBUKA HIJAU KAMPUS : STUDI KASUS DI KAMPUS II UNIVERSITAS MUHAMMADIYAH PALANGKARAYA - Ardiyansyah Purnama; Mariaty Mariaty; Norma Wijayanti (Jurusan Kehutanan -FHIL-UHO, 2024)
Global climate change has increased attention to soil carbon storage as one of the mitigation efforts. This study aims to assess the potential of soil carbon storage in the green open space of Campus II of Muhammadiyah University of Palangkaraya. The research was conducted in March-July 2024 using 15 plots with a 20x20 m plot method. Parameters analyzed included soil bulk density, porosity, soil pH, C-organic content, and soil carbon storage. The results showed that the average bulk density value was 1.46 g/cm³, with a porosity of 55.84%. The average soil pH value was 5.1, classified as acidic. The highest C-organic content was found in plots 13 and 14, at 5.73% and 5.69% respectively. Plot 10 had the highest carbon storage at 6888 tons/ha, supported by high C-organic content, optimal stand density, and minimal human disturbance. This study shows that green open space management that considers soil and vegetation characteristics can increase carbon storage, in line with the green campus concept for climate change mitigation.